The evaluation of efficacy of atmospheric pressure plasma in diabetic ulcers healing: A randomized clinical trial. Issue 6 (29th October 2021) - Samsavar, Shirin; Mahmoudi, HamidReza; Shakouri, Reza; Khani, Mohammad Reza; Molavi, Behnam; Moosavi, Jamal; Daneshpazhooh, Maryam; Etesami, Ifa; Shokri, Babak
Abstract: The aim of this study is to evaluate the efficacy and safety of cold atmospheric plasma (CAP) as a novel therapy for diabetic foot ulcers. This was an investigator‐blinded, randomized controlled trial of 14 weeks (6 weeks of treatment and 8 weeks of follow‐up). Twenty patients with diabetic foot ulcers were divided into two groups: the control group receiving standard wound care and the plasma group, which received CAP twice a week for six consecutive weeks in addition to standard wound care. The ulcer size, amount of exudate, and wound grading were determined weekly. Cold plasma was produced by applying a high voltage (4.5 kV) and a high frequency (22 kHz) to helium gas. Exudate from wounds treated with CAP showed a significant reduction in the third week after complete treatment ( p  = 0.039). The wound grading of the ulcers improved by the sixth week ( p  = 0.019), and the sizes of ulcers significantly decreased in the plasma group at the end of the treatment period ( p  = 0.007). In this randomized clinical trial, CAP was an effective treatment option for diabetic foot ulcers in terms of wound surface reduction and antibacterial effects.